2008 19th International Conference on Database and Expert Systems Applications 2008
DOI: 10.1109/dexa.2008.118
|View full text |Cite
|
Sign up to set email alerts
|

Time Efficient Service Discovery in Mobile P2P Architectures Using Bluetooth

Abstract: Key challenges in mobile ad-hoc networks are computational resource constraints, power limitations and time delays in information exchange. Therefore it is necessary to develop intelligent, efficient indexing strategies for knowledge addressing and exchange in dynamic mobile P2P architectures. The short range radio technology Bluetooth suffers from long service discovery delays and high power consumption due to required connection establishment based on its Service-Discovery-Protocol (SDP). To overcome this si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In a two day test we observed that the device inquiry time T inq is always about 7-12 s. It varies around about 5 s due to moving Bluetooth peers during our test (each test lasted about one hour). The results are presented at [9]. The native SDP requires successive connection establishments to all devices within the environment.…”
Section: A Time Efficient Service Discovery Using Bluetoothmentioning
confidence: 98%
See 2 more Smart Citations
“…In a two day test we observed that the device inquiry time T inq is always about 7-12 s. It varies around about 5 s due to moving Bluetooth peers during our test (each test lasted about one hour). The results are presented at [9]. The native SDP requires successive connection establishments to all devices within the environment.…”
Section: A Time Efficient Service Discovery Using Bluetoothmentioning
confidence: 98%
“…Discovering services often takes a lot of time and produces a lot of network traffic as we present in Section 4. To overcome this situation in Bluetooth environments with high node concentrations we try to improve the native Service-Discovery-Protocol (SDP) by service meta data indexing as outlined in [9]. After all we are able to pre-filter data or information services on inquiry.…”
Section: A Efficient Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make this process seamless and yet maintain security in the communications, we have modified the authentication process by overriding the Bluetooth pairing and instead developed a hashkey generator to broadcast a shared key to proximate users who are using the same software client. Searching involves using L2CAP [67] as the physical layer and combination of SDP [68] and TCP/IP for higher layers. Figure 3.10 shows how the proposed pairing process works in an ad hoc setting.…”
Section: Pairing and Discovery Modulesmentioning
confidence: 99%
“…This layer provides the functionality to confirm the services are running by a Bluetooth device. SDP discovers the service running on different devices (Peters & Heuer, 2008), and finds the parameters to use to connect to different devices. This layer uses an L2CAP device for discovery and connection.…”
Section: Service Discovery Protocol (Sdp)mentioning
confidence: 99%